EVALUASI DAN PENETAPAN LAHAN PERTANIAN BERKELANJUTAN UNTUK PENCEGAHAN ALIH FUNGSI LAHAN DI KABUPATEN BANGLI - I Made Adnyana; I Nyoman Puja; I Dewa Made Arthagama (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2017)
EVALUATION AND DETERMINATION OF SUSTAINABLE LAND AGRICULTURE FOR PREVENTION OF LAND CONVERSION IN BANGLI REGENCYThe research was done in the area of ??paddy soil in Bangli District, Bangli Regency to identification, evaluation, and mapping the paddy soil area that have to maintain as a sustainable agriculture. To achieve these objectives, the research conducted through several activities, namely: soil survey and environment, physical and chemistry of soil analysis, and mapping the model of the prevented exchangeable paddy soil functions. Depend on plan lay out space (called RTRW) of Bangli regency, there were two models of sustainable agriculture decision at district of Bangli, where in each model, land (Subak) mapping as subak everlasting, subak buffer, and Subak convertion. Subak convertion was have opportunity to changing function. Subak convertion of Model I as 158,68 ha (2011 – 2021) and Model II as 78,14 ha (2021 – 2031) respectively.